Menulis Ulang Perseteruan Islam dan Komunisme di Afganistan - Widuatie, Ratna Endang; Salindri, Dewi; Handayani, Sri Ana; Rosyidah, Nur (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2023)
This article discusses the impact of the clashof two political forces in Afganistan,the Islamic faction and the communist faction, from the 1960s to the 2000s. An important change in Afganistan’s history occurred when the Soviet Union’s military intervention ended and Islamic groups took control. However, the next change occurred when the United States invaded, which dwarfed Islam in the country’s political agenda, which ultimately triggered the seizure of power by the Taliban. Previous studies on Afganistan provide an overview of the patterns of change and power that occurred in Afganistan. The narrative that developed about Afganistan, especially when the Taliban group came to power, opened up opportunities for new discourses in looking at the relationship between Islam and secular political forces, especially communist in this Central Asian country. This article was prepared using historical method to obtain an explanation of the political dynamics of Afganistan in the second half of the 20th century to the beginning of the 21st century. The political science approach as an auxiliary tool helps to understand several unique symptoms in the case of Afganistan, including the relationship between Islam and communism, the international views of both the West and the Islamic world towards modern Afganistan, and the significance of rewriting Afghan history, especially in conflict studies. These topics are key to placing Afganistan in the interrelated discussion of regional history and geopolitics.